Garantia literária: elementos para uma revisão crítica após um século - Barité, Mario; Fernández-Molina, Juan Carlos; Guimarães, José Augusto Chaves [UNESP]; Moraes, João Batista Ernesto de [UNESP] (Pontifícia Universidade Católica de Campinas, 2010)
This study contributes to a critical synthesis of the principle of literary warrant, initially formulated by Hulme in 1911. Hulme proposed that the terms of a classification system should be derived from the literature to be classified, rather than based on purely theoretical considerations. Founding literary warrant on literature which is actually documented rather than on scientific or philosophical classifications or on the supposed authority of the first classificationists implied a clear departure from the conceptions of Harris and Dewey, who had used the classifications of Bacon and Leibniz as models. The validity of this principle over the past century is studied by means of diverse documental data (entries in dictionaries, retrieval by Google, etc.), as it is recognized as a main methodological element for classification standards and systems. This study also discusses the situation with respect to the top-down or bottom-up methodologies of system design. Three traditional applications of literary warrant are described as well as three new applications are suggested, in light of its methodological potential. It is possible to conclude that this principle will find increasing applications in other contexts, within and beyond Information Science.
Literary warrant: elements for a critical review after one century
Keywords: Literary warrant; Knowledge organization systems; Controlled vocabularie